A mex3 homolog is required for differentiation during planarian stem cell lineage development - Shu Jun Zhu; Stephanie E Hallows; Ko W Currie; ChangJiang Xu; Bret J Pearson (eLife, 2015)
Neoblasts are adult stem cells (ASCs) in planarians that sustain cell replacement during homeostasis and regeneration of any missing tissue. While numerous studies have examined genes underlying neoblast pluripotency, molecular pathways driving postmitotic fates remain poorly defined. In this study, we used transcriptional profiling of irradiation-sensitive and irradiation-insensitive cell populations and RNA interference (RNAi) functional screening to uncover markers and regulators of postmitotic progeny. We identified 32 new markers distinguishing two main epithelial progenitor populations and a planarian homolog to the MEX3 RNA-binding protein (Smed-mex3-1) as a key regulator of lineage progression. mex3-1 was required for generating differentiated cells of multiple lineages, while restricting the size of the stem cell compartment. We also demonstrated the utility of using mex3-1(RNAi) animals to identify additional progenitor markers. These results identified mex3-1 as a cell fate regulator, broadly required for differentiation, and suggest that mex3-1 helps to mediate the balance between ASC self-renewal and commitment.